An Examination of the Nexus Between Ethical Leadership and Corporate Governance and its Impact on Organizational Performance: Evidence from MTN Nigeria - Odunsi Adenike Olufunmilayo; Enyioko Chilaka Onyekachi; Odeniyi Kolapo Demilade (ZBW - Leibniz Information Centre for Economics, 2025)
This study investigated the nexus between ethical leadership and corporate governance and their collective impact on organizational performance, using MTN Nigeria as a case study. Anchored in stakeholder and agency theoretical frameworks, the research examined how ethical behavior at the leadership level and structured governance mechanisms reinforce organizational effectiveness. A descriptive survey design was employed, involving a stratified random sample of 360 employees across top, middle, and lower management tiers. Data were collected using a validated questionnaire (Cronbach's Alpha = 0.88) and analyzed using SPSS version 27.0. Descriptive statistics indicated a high perception of ethical leadership practices, with a grand mean of 3.67 (SD = 1.06), and a strong rating for corporate governance effectiveness with a grand mean of 3.85 (SD = 1.10).Inferential results from multiple regression analysis showed that ethical leadership and corporate governance jointly accounted for 63.2% of the variance in organizational performance (R² = 0.632, Adjusted R² = 0.463, F(7, 352) = 42.36, p﹤ 0.0001). Among the predictors, ethical leadership transparency (β = 0.244, p﹤ 0.0001) and governance enforcement (β = 0.189, p﹤ 0.0001) emerged as the most significant drivers of performance. These findings highlight that organizations like MTN Nigeria that institutionalize ethical standards and governance compliance outperform those that do not. The study concludes that ethical leadership provides the moral compass for governance, while sound governance structures embed ethical principles into strategic decision-making. It recommends enhanced leadership training and periodic governance audits to sustain long-term organizational excellence.
Keywords: 330; Ethical Leadership; Organizational Performance; Corporate Governance; Transparency